ANALISIS MODEL MODAL SOSIAL TERHADAP KEBERDAYAAN PETANI KARET DI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Ii Humaidi; Ahmad Rifai; Kausar Kausar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The objective of this research is to identified the social capital of the rubber farmer’s that affecting to the empowerment of farmers and its affect on the prosperity of rubber farmers in XIII Koto Kampar subdistrict, Kampar district. The social capital and the empowerment of rubbers farmer was identified by the likert scale and the relationship of the social capital and empowrment of rubbers farmers was analyzed by the Spearman Rank correlation. The result of study shown that the social capital of the rubber farmers in high categorized. The high social capital was built by the high social network, high social trust and high norm. The empowermrnt of the rubber farmers was medium, that support by the medium empowermrnt in economic and medium empowerment in social. Based on Spearman Rank analysis fount that there is no relationship the dimension of social capital and empowerment of the rubber farmers. Keywords: social capital, empowerment, rubber farmer